아미노산 비료가 크리핑 벤트그래스의 생육과 질소 흡수에 미치는 영향 - 김영선(Young-Sun Kim); 함선규(Suon-Kyu Ham); 이재필(Jae-Pil Lee); 황영수(Young-Soo Hwang); 이규승(Kyu-Seong Lee) (Weed & turfgrass science, 2014)
This study was conducted to evaluate the effects of two amino acid fertilizers on the growth of creeping bentgrass and N uptake. Fertilizer treatments were designed as follows; non-fertilizer (NF), control (CF), recommended amount (ALF), double amount (2ALF) of amino acid liquid fertilizer (AaLF), recommended amount (ASLF) and double amount (2ASLF) of amino acid liquid fertilizer contained with saponin (AaSLF). Turf quality of treatments of AaLF and AaSLF such as turf color index, chlorophyll index and root length was similar to the treatment of CF. Dry weight and content, uptake and availability of N were investigated highest in the 2ALF and 2ASLF. These results suggested that foliar application of AaLF and AaSLF was enhanced turf quality and growth of creeping bentgrass by stimulating uptake and availability of N. 본 연구는 두 종류의 아미노산 비료를 엽면시비하여 크리핑 벤트그래스의 생육효과를 평가하기 위해 수행되었다. 처리구를 비료의 종류와 시비량에 따라 무처리구(NF), 대조구(CF), 아미노산 비료 정량 처리구(ALF)와 배량 처리구(2ALF), 아미노산-사포닌 비료 정량 처리구(ASLF) 및 배량 처리구(2ASLF)로 설정하여 처리한 후 엽색지수, 엽록소지수, 건물중, 잔디 밀도, 뿌리 길이 및 잔디의 양분 함유량 등을 조사하여 생육을 평가하였다. 잔디의 품질을 나타내는 엽색지수와, 엽록소지수, 잔디 밀도 및 잔디 뿌리 길이는 CF와 비슷하거나 약간 높았다. 잔디의 생육을 나타내는 건물중과 잔디 중 질소와 칼리 함량, 질소 흡수량 및 이용율은 2ALF와 2ASLF구에서 높았다. 이러한 결과를 통해 아미노산 비료(AaLF)와 아미노산-사포닌 비료(AaSLF)의 시비가 잔디의 질소 흡수 및 이용율이 증가하여 잔디 잔디생육과 잔디 품질을 향상시키는 것을 알 수 있었다.